Implementasi Metode Takrir dalam Meningkatkan Tazwidul Mufradat Siswa Kelas X MA PPMI Assalam Sukoharjo - Fakhrudin, Fatah Fuad; Inayati, Nurul Latifatul (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Arabic learning has many methods that teacher can use in delivering material to students well. One of them is by using the takrir method. Madrasah Aliyah PPMI Assalaam Sukoharjo is a school that applies using Arabic in its daily activities. However, there are some students who think that Arabic is a difficult subject to learn. Therefore, as one of the efforts of the language section teacher requires the application of good methods in learning Arabic, the solution is to use the takrir method in the application of tazwidul mufradat activities. The research method used is a qualitative method with a phenomenological approach involving data collection by observation, interviews and documentation. The purpose of this study is to determine the application of the takrir method in improving the ability to memorize mufradat (vocabulary) Tazwidul mufradat activities and their supporting and inhibiting factors. The results of this study explain that the takrir method has proven effective in improving the memorization ability of mufradat (vocabulary) students of MA PPMI Assalaam. The achievement of students can be seen from the course of Tazwidul Mufrodat activities can be seen from the course of activities. The supporting factors of this method are efficient timing, strong memorization and fluency of Arabic pronunciation. The inhibiting factors are boredom, limited understanding, and limited evaluation.